2017 25th European Signal Processing Conference (EUSIPCO) 2017
DOI: 10.23919/eusipco.2017.8081690
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diverse preprocessing pipelines on brain functional connectivity

Abstract: Abstract-Brain functional connectivity measured by functional magnetic resonance imaging was shown to be influenced by preprocessing procedures. We aim to describe this influence separately for different preprocessing factors and in 20 different most used preprocessing pipelines. We evaluate the effects of slice-timing correction and physiological noise filtering by RETROICOR, diverse levels of motion correction, and white matter, cerebrospinal fluid, and global signal filtering. With usage of three datasets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The effect of rsfMRI processing decisions on analysis is a large and important issue to address that is beyond the scope of our Challenge, but has been investigated by others (see e.g. Bowring et al (2019); Výtvarová et al (2017); Vergara et al (2017)). We note that a subset of the rsfMRI data has been released through ABIDE (Di Martino et al (2013)) and ADHD-200 9 .…”
Section: Challenge Contributionsmentioning
confidence: 99%
“…The effect of rsfMRI processing decisions on analysis is a large and important issue to address that is beyond the scope of our Challenge, but has been investigated by others (see e.g. Bowring et al (2019); Výtvarová et al (2017); Vergara et al (2017)). We note that a subset of the rsfMRI data has been released through ABIDE (Di Martino et al (2013)) and ADHD-200 9 .…”
Section: Challenge Contributionsmentioning
confidence: 99%
“…The dataset also contained simultaneously recorded ECG and respiration, which allowed us to pre-process fMRI data by RETROICOR. And finally, we tried many pre-processing strategies [79] to test their effect on functional connectivity estimation. For this study, we were able to select the best pipeline with the highest signal-noise separation (SNS) parameter [80].…”
Section: Limitationsmentioning
confidence: 99%
“…Much work documenting the influence of denoising strategy on network topology has been conducted in young healthy adults (Aurich et al, 2015; Liang et al, 2012; Ciric et al, 2017; Vỳtvarová et al, 2017; Yan et al, 2013). A strength of the current investigation was that analyses were conducted in older adults at different stages of the AD continuum.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focus on the potential impact of preprocessing decisions, specifically denoising strategy, on AD diagnostic differences in graph metrics. An emerging literature provides evidence that the steps included and order of preprocessing pipelines affects the reliability of functional connectivity estimations and ultimately graph metrics (Alakörkkö, Saarimäki, Glerean, Saramäki, & Korhonen, 2017; Aurich, Alves Filho, Marques da Silva, & Franco, 2015; Borchardt et al, 2016; Liang et al, 2012; Ran et al, 2020; Vỳtvarová et al, 2017; Yan, Craddock, He, & Milham, 2013). For instance, Liang and colleagues (2012) found that preprocessing pipelines excluding global signal regression and including a wide bandpass frequency range (0.02-0.07) produced the most reliable topological estimates.…”
Section: Introductionmentioning
confidence: 99%